A Detailed Study On Features of Data Warehousing Database-Vertica - Jose, Jisha Mariam (International Journal of Computer Sciences and Engineering, 2025)
The data which are to be stored and analyzed for various purposes have gone beyond the storage limit of the traditional relational database system. This has led in emerge of various big data technologies to store and process this huge collection of varieties of data. Vertica is an HP enterprise product, which is used in data warehouses to store and perform data analysis that are stored for decades. Vertica is not only used in data warehouses but also it can be integrated with Hadoop ecosystem for big data analysis. This paper basically describes the architecture, features, storage, various operations in Vertica analytics database that has made Vertica to be used for managing and analysis of large volumes of fast-growing data for achieving higher performance in query intensive applications and data warehouses.